Building Sustainability in Higher Education through Green Management and Innovation: A Case Study of Private Universities in Jakarta - Sutawaidjaya, Ahmad Hidayat; Yusuf, Muhammad; Hamdi, Edi (Journal of Ecohumanism, 2024)
This study analyzes the causal relationship between green management, supply chain management, and organizational culture on the sustainability of higher education institutions, with green innovation as a mediating factor. Data were collected from private universities in Jakarta and compared with global benchmarks such as the Times Higher Education Impact Rankings and the UI GreenMetric World University Rankings. Using SEM-PLS for analysis, the results show that green management, supply chain management, and organizational culture each positively influence the sustainability of higher education institutions. The study demonstrates how green management practices and organizational culture affect sustainability in higher education. International comparisons reveal similar trends globally, with green innovation playing a crucial mediating role.